2022
DOI: 10.1186/s12889-022-12984-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of long-term exposure to PM2.5 with hypertension and diabetes among the middle-aged and elderly people in Chinese mainland: a spatial study

Abstract: Background Epidemiological evidence has shown an association between long-term exposure to fine particulate matter (PM2.5) and hypertension and diabetes, but few studies have considered the spatial properties of the samples. This study aimed to investigate the long-term effect of PM2.5 exposure on hypertension and diabetes among middle-aged and elderly people in China based on a spatial study. Methods We conducted a national cross-sectional study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…PM 2.5 exposure has been shown to be associated with an increased risk of cardiometabolic risk factors and cardio-cerebrovascular diseases 9 . Cross-sectional evidence from the China Health and Retirement Longitudinal Study (CHARLS) among 19,529 participants has demonstrated that an increase in PM 2.5 concentration is significantly associated with a higher prevalence of hypertension (OR = 1.07, 95% CI = 1.03 to 1.11) and diabetes (OR = 1.15, 95% CI = 1.10 to 1.20), with the impact being relatively stronger in nonsmokers than smokers 30 . Additionally, exposure to both household and outdoor air pollutants has been linked to an increased risk of angina pectoris and myocardial infarction (MI) 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…PM 2.5 exposure has been shown to be associated with an increased risk of cardiometabolic risk factors and cardio-cerebrovascular diseases 9 . Cross-sectional evidence from the China Health and Retirement Longitudinal Study (CHARLS) among 19,529 participants has demonstrated that an increase in PM 2.5 concentration is significantly associated with a higher prevalence of hypertension (OR = 1.07, 95% CI = 1.03 to 1.11) and diabetes (OR = 1.15, 95% CI = 1.10 to 1.20), with the impact being relatively stronger in nonsmokers than smokers 30 . Additionally, exposure to both household and outdoor air pollutants has been linked to an increased risk of angina pectoris and myocardial infarction (MI) 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in this study, the overall prevalence of DPN was 50.1%, and the prevalence of DPN in Xinjiang was 51.5%, higher than the 45.7% in Suzhou, Jiangsu Province, which may be due to regional differences as the diet in Xinjiang is known to include more chili oil and salty in comparison to other regions. According to the results of the latest national cross-sectional study [ 43 ], Xinjiang has the highest prevalence of diabetes in in the country, which may be the reason for the high prevalence of DPN. By verifying the AUC area of the dataset (the AUC of the validation group is greater than the AUC of the training group), the model has a wide range of versatility.…”
Section: Discussionmentioning
confidence: 99%
“…Also, hypertension is a basic disease of the elderly. 46 The low dose (2 mg/kg) of azelnidipine was calculated according to the clinical dose. 47 Then our studies showed that azelnidipine inhibited the growth of the PDX model of ESCC in vivo ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%